DA.Vra1-congenic rats display increased gene expression and Schwann cell apoptosis but unaffected nerve regeneration compared to parental DA rats after sciatic nerve injury and repair - Stenberg, Lena; Jewett, Michael; Dueñas Rey, Alfredo; Swanberg, Maria; Dahlin, Lars B. (Frontiers in Cell and Developmental Biology, 2025)
IntroductionThe rat Vra1 locus, containing glutathione S-transferase alpha 4 (Gsta4), regulates the degeneration of central nervous system (CNS) neurons in toxin-, protein-, and injury-based models. We hypothesize that Piebald Virol Glaxo.1AV1 (PVG) alleles in Vra1 confer protection and increased axonal outgrowth after peripheral nerve injury and repair.MethodsDA rats (n = 14) and DA rats with PVG alleles in the Vra1 locus (DA.Vra1, n = 14) were subjected to sciatic nerve transection and immediate repair. After 6 days, axonal outgrowth and protein and gene expression were analyzed in injured and uninjured nerves and dorsal root ganglia (DRG).ResultsNo differences in axonal outgrowth were observed between strains, but the number of apoptotic Schwann cells in the injured distal nerve end was higher in DA.Vra1 than in DA rats (p = 0.003). In both strains, gene- and protein expression of activating transcription factor 3 (ATF3) and 27-kDa heat shock protein (HSP27, i.e., Hspb1) were increased in injured vs. uninjured DRG. In DA.Vra1 rats, Gsta4 gene expression was lower in injured vs. uninjured DRG (p = 0.043) but higher than in DA rats in injured nerves (p = 0.008) and injured DRG (p = 0.008). DA.Vra1 had higher gene expression of Atf3 (p = 0.016) and caspase 3 (p = 0.032) in injured nerves than DA rats.DiscussionResults highlight the complexity of nerve injury and repair, supporting further investigation of Gsta4 in nerve regeneration.